An economic production quantity (EPQ) model for a deteriorating item with partial trade credit policy for price dependent demand under inflation and reliability - Shaikh, Ali Akbar; Cardenas-Barron, Leopoldo Eduardo; Manna, Amalesh Kumar; Cespedes-Mota, Armando (Yugoslav Journal of Operations Research, 2020)
It is well-known that the production-inventory problem for deteriorating items in the supply chain is a challenge at the time to decide on how many products to manufacture with the aim of obtaining a maximum total prot. This research work develops an economic production quantity model for a deteriorating item under partial trade credit policy considering the inflation, the effect of the reliability factor of the production system, and that the demand depends on the price of the product where the selling price is optimized. The production-inventory model is formulated as a nonlinearly constrained optimization problem by analyzing different cases. Finally, through a numerical example, a sensitivity analysis is performed with the aim of studying the effect of different parameters; changing one of them at a time and keeping the others fixed at their original values.